(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The zygomatic arch is a complex formed by the temporal process of the zygomatic bone. Quite often, fractures of the zygomatic arch proper are observed, which do not extend to the body of the zygomatic bone and its other processes